A relação entre uso de vídeo games e funções executivas em crianças - Costa, Oaní da Silva da (Universidade Federal de São Carlos, 2019)
Electronic games are part of our daily lives and it is difficult to find somebody who never had had contact with this tool, especially children. One of the key points to be investigated from this interaction is its relation to human cognition. So, the present study had the goal of checking for differences between groups of players and non-players regarding performance in instruments that access EFs, considering socioeconomic values, gender and age differences as well. Besides that, calculate correlations between the EF tests and gameplay time, socioeconomic level and times of leisure and extra-curricular activities. To do so, 86 children in the age range of 7 to 10 years answered an instrument that access executive functions, the Five Digits Test. Participants also answered the “Questionário de Experiência com Videogames e Outras Atividades” to acess video game practice. After that, two groups were formed, one with higher video game frequency (players) and other with low or no frequency of play (non-players). The caretakers of the participating children were also invited to answer the “Inventário de Dificuldades em Funções Executivas, Regulação e Aversão ao Adiamento para crianças - IFERA-I” that access executive functions and the “Questionário Socioeconômico Critério Brasil”. Analyses of the data revealed that there were no significant differences between players and non-players without considering age, or, video game play wasn’t a relevant variable to explain scores that access executive functions. But by separating the groups by age, the data showed low negative effect of gameplay. The data also showed that there were no differences between playing and not playing relative to sex and socioeconomic scores.
The relation between the use of videogames and executive functions in children
Keywords: Vídeo games; Funções executivas; Cognição; Executive functions; Cognition; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::PROCESSOS COGNITIVOS E ATENCIONAIS